Hakikat Manusia dalam Pendidikan Islam - Salsabila Salsabila; Yurna Yurna; Venti Fatmawati Suhendra; Ai Siti Rahmawati; Aat Yuniawati (Asosiasi Riset Ilmu Pendidikan Agama dan Filsafat Indonesia, 2026)
The concept of human nature occupies a fundamental position in the philosophy of Islamic education, as it serves as the foundation for formulating educational goals, curriculum design, teaching methods, and the overall direction of education. Islamic education is not merely oriented toward the transfer of knowledge but is directed toward shaping the whole human being in a balanced manner, encompassing physical, intellectual, and spiritual dimensions. This study aims to examine the concept of human nature from the Islamic perspective and the views of Islamic philosophical figures, as well as to analyze its philosophical and practical implications for the implementation of Islamic education. This research employs a library research method by reviewing primary and secondary sources, including the Qur’an, classical Islamic texts, and relevant scholarly literature on human nature and Islamic education. The findings indicate that Islam views human beings as multidimensional creatures endowed with fitrah, intellect, spirituality, and social responsibility as servants and vicegerents of God on earth. The Qur’anic concepts of humanity, reflected in the terms al-insān, al-basyar, and al-nās, emphasize the complexity and uniqueness of humans as biological, rational, spiritual, and social beings. The perspectives of scholars such as Al-Ghazali, Ibn Arabi, and Hasan Al-Banna further reinforce the view that Islamic education must integrate intellectual, moral, and spiritual development in a balanced manner. The implications of this study highlight the necessity of designing Islamic education in a holistic and humanistic framework to produce insan kamil—individuals who are faithful, knowledgeable, possess noble character, and demonstrate social responsibility in communal life.